2023
DOI: 10.1002/jat.4445
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[b]fluoranthene induced oxidative stress and apoptosis in human airway epithelial cells via mitochondrial disruption

Abstract: Benzo[b]fluoranthene (BbF) is a common constituent of polycyclic aromatic hydrocarbons (PAHs). While numerous studies revealed adverse effects of PAHs on human health, the health effects of individual PAHs differ, and few investigations were performed on BbF. Therefore, the present study established cytotoxicity models of human lung epithelial cells (BEAS‐2B cells) and bronchial epithelial cells (16HBE cells) exposed to BbF (10, 20, and 40 μM) for 24 h to reveal the mechanisms. Results from cytotoxicity and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Scientific evidence revealed that apoptosis is activated in response to oxidative stress [72][73][74]; however, chronic exposure to pro-oxidant agents may impair this mechanism of programmed cell death, thus likely favouring the survival and further degeneration of damaged cells [75]. In this respect, Shim et al [76] reported that cells stimulate apoptotic processes as a defense mechanism to prevent viral replication, while the virus tends to inhibit this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific evidence revealed that apoptosis is activated in response to oxidative stress [72][73][74]; however, chronic exposure to pro-oxidant agents may impair this mechanism of programmed cell death, thus likely favouring the survival and further degeneration of damaged cells [75]. In this respect, Shim et al [76] reported that cells stimulate apoptotic processes as a defense mechanism to prevent viral replication, while the virus tends to inhibit this mechanism.…”
Section: Discussionmentioning
confidence: 99%